2023
DOI: 10.3390/cli11050106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydrometeorological Trends and Drought Severity in Water-Demanding Mediterranean Islands under Climate Change Conditions

Abstract: Global climate change has emerged as a problem in recent years, and its effects will likely continue to increase in the future. Several scientific studies conducted in the Mediterranean region have demonstrated relatively stationary trends for annual precipitation and significant upward trends for mean annual temperature. These trends present several implications, especially in the Greek islands that serve as major summer tourist destinations where the population is already unable to meet their water demands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Taking as an example the case of Greece, regional precipitation trends in recent years are mostly stationary, with a few of them positive/negative and significant (Margaritidis, 2021;Sakalis, 2022;Stathi et al, 2023). On the other hand, in the case of temperature, a statistically significant increase in air temperature in recent decades is more pronounced (Proutsos et al, 2020Kastridis et al, 2022Stathi et al, 2023). However, the investigation of regional trends is beyond the scope of the present study.…”
Section: Temperature Trendsmentioning
confidence: 75%
See 2 more Smart Citations
“…Taking as an example the case of Greece, regional precipitation trends in recent years are mostly stationary, with a few of them positive/negative and significant (Margaritidis, 2021;Sakalis, 2022;Stathi et al, 2023). On the other hand, in the case of temperature, a statistically significant increase in air temperature in recent decades is more pronounced (Proutsos et al, 2020Kastridis et al, 2022Stathi et al, 2023). However, the investigation of regional trends is beyond the scope of the present study.…”
Section: Temperature Trendsmentioning
confidence: 75%
“…Precipitation trends are relative to several factors, such as the altitude of the region, orientation, distance from the sea, etc. Taking as an example the case of Greece, regional precipitation trends in recent years are mostly stationary, with a few of them positive/negative and significant (Margaritidis, 2021;Sakalis, 2022;Stathi et al, 2023). On the other hand, in the case of temperature, a statistically significant increase in air temperature in recent decades is more pronounced (Proutsos et al, 2020Kastridis et al, 2022Stathi et al, 2023).…”
Section: Temperature Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of the necessary water exploitation projects, mainly for the surface runoff, has led to the intense water supply problems that the islands struggle with. The necessity of the water harvesting projects becomes even more important, under the conditions of significant increases in temperature [9,[65][66][67][68][69], where the increase in evapotranspiration constitutes a highly likely scenario, especially in arid and semi-arid regions. Previous studies conducted in the Mediterranean region revealed that under various climate change scenarios, the water balance could be significantly affected.…”
Section: Total Water Demandmentioning
confidence: 99%
“…Quantifying the groundwater recharge rate is necessary for effective and long-term groundwater management [11]. This results from ongoing global environmental changes, such as climate change, land use changes, and, ultimately, adaptation processes; hence, it is crucial to determine how these changes will affect groundwater recharge and resources [12,13].…”
Section: Introductionmentioning
confidence: 99%